Urgensi Pendidikan Akhlak Dalam Pembentukan Kecerdasan Spiritual Pada Siswa Program Unggulan Di MTs Negeri Berbek, Nganjuk (FAI- Undar, 2021)
Research in the background of this thesis by the reality of a society that is dominated by spiritual poverty which resulted in suffering and the destruction of areas of our national life. For that, they need moral education to achieve balanced growth of the human self Muslims thoroughly through psychiatric practice, reasonable minds, intelligence, feelings, and senses so as to have a major personality. Therefore, Muslim educators must develop all aspects of human life both spiritually, intellectually, imagination (fantasy), physical, scholarly, language, and encouraging aspects of it toward goodness or perfection of life. The purpose of this study was to determine (1) Implementation of Education Akhlak the featured student at MTs Berbek. (2) The urgency of morality in shaping education spiritual intelligence featured students at MTs Berbek. (3) Efforts to improve intelligence spiritual teacher to the students featured in Berbek MTs. This study uses qualitative research by conducting in-depth interviews, participant observation and documentation. In-depth interviews are used to collect information on moral education to the students featured in the form of spiritual intelligence. While the method of participant observation was used to observe the efforts of teachers in improving the spiritual intelligence and observe the behavior of the students featured, while documentation is used to collect data on populations, samples, educational facilities and school documents. Based on the research that has been done, the authors found several findings include: (1) Implementation of moral education in the flagship program through moral education method, the arrangement of the material and its implementation. For example: the material morality commendable familiarize reflected in the mix ordinances students who value friends, teachers and elders. (2) The urgency of moral education in an effort to establish the spiritual intelligence featured student is, with the superior morality that can lead to spiritual intelligence to the character formation of the students, among other things: prayer fardlu diligent student and sunnah prayers, diligently reading the Koran, practicing independent in solving the problems faced and put my trust in Allah. (3) Efforts to improve spiritual intelligence in a way: give good role models of teachers and parents, familiarize students to pray Duha, istighotsah and tahtimul Qur'an, invites students to evening prayer.